Respuesta :

Answer:  (-1, 6)

==============================================================

Explanation:

f(x) is equal to both x^2-2x+3 and also -6x at the same time. Set those two expressions equal to one another and solve for x.

x^2-2x+3 = -6x

x^2-2x+3+6x = 0

x^2+4x+3 = 0

(x+3)(x+1) = 0 .... see note below

x+3 = 0 or x+1 = 0

x = -3 or x = -1

Note: 3 and 1 multiply to 3, and also add to 4.

---------------------

Once we get the x values, we plug them into either equation to find the y value.

So if x = -3, then

f(x) = x^2-2x+3

f(-3) = (-3)^2-2(-3)+3

f(-3) = 9 + 6 + 3

f(-3) = 18

or we could say

f(x) = -6x

f(-3) = -6(-3)

f(-3) = 18

Both versions produce the same output when x = -3.

The second version is easier to work with.

Since x = -3 leads to y = 18, we know that (-3, 18) is one of the solutions. That explains where your teacher got (-3, 18) from.

-----------

We'll use this idea for x = -1 now

f(x) = x^2-2x+3

f(-1) = (-1)^2-2(-1)+3

f(-1) = 1 + 2 + 3

f(-1) = 6

or we could say

f(x) = -6x

f(-1) = -6(-1)

f(-1) = 6

Like before, both versions of f(x) produce the same output when the input is x = -1.

The other solution is (-1, 6)

ACCESS MORE